Scenarios for oil palm expansion in degraded and deforested lands in the Brazilian Amazon to meet biodiesel demand - Carvalho, Carolina Monteiro de; Iwama, Allan Yu; La Rovere, Emilio (Sustainability in Debate, 2021)
Palm oil production for biodiesel in Brazil is characterized by its high productivity in some environmental conditions, under the Sustainable Palm Oil Production Program. The program seeks to avoid deforestation for oil palm cultivation, recover degraded lands, and focus on social inclusion and family farming. This paper assesses the possible socio-environmental impacts of the expansion of palm oil until 2030, focusing on land-use change and impacts. Land-use data came from the TerraClass initiative for the analysis of degraded forests using geoprocessing. We produced two oil expansion scenarios. The first one reflects current trends in palm oil production expansion and deforestation in Pará State (S1). The second one considers the exclusive use of deforested/degraded land for oil palm crops (S2). The results demonstrate that degraded/deforested land in the current palm oil-producing municipalities is only sufficient for the projected level of expansion for 2020, requiring a stronger public policy to recover degraded areas for oil palm cultivation with social inclusion of family farming.